Group Guidance Services Assisted by Learning Animation Video on Students’ Learning Activeness as Pancasila Learners in Elementary School - Suharjono, Gilang Eko Setyo; Fitriyah, Chumi Zahroul; Finali, Zetti; Hutama, Fajar Surya; Puspitaningrum, Dyah Ayu (Universitas Pendidikan Ganesha, 2025)
The low level of student learning activity makes the learning process less effective. Counselling services are needed to overcome the low learning activity level through group guidance services. This study aims to analyse the effect of group guidance services assisted by animated learning videos on student learning activity as fourth-grade Pancasila learners. This study is experimental with a quasi-experimental design through a nonequivalent control group posttest-only pattern. The research subjects were 15 in grade IV-A and 15 in grade IV-B. The data collection technique was observation. The research instrument was an observation sheet as a posttest. The data analysis technique used inferential statistical analysis. The results of the descriptive percentage test showed a higher percentage in the experimental class than in the control class. In the experimental class, meeting 1 (66.8%), meeting 2 (76.5%) and meeting 3 (89.0%) and in the control class, meeting 1 (63.9%), meeting 2 (71.3%) and meeting 3 (78.5%). The results of the t-test obtained t count (3.476) > t table (2.048), then Ha is accepted and H0 is rejected, so it can be concluded that there is an influence of group guidance services assisted by animated learning videos on student learning activity as Pancasila learners in grade IV. The implications of this study indicate that group guidance services assisted by animated learning videos can effectively increase student learning activity among Pancasila learners in elementary schools.